ANALISIS AL-FI’IL MUDHARI’ AL-MABNI DAN BINA ALHURUF DALAM KAJIAN ILMU NAHWU KLASIK DAN KONTEMPORER - Hatnima Hannum; Anwar Sidik (Universitas Muhammadiyah Makassar, 2026)
This study addresses the issue of how the concept of al-fiʿil al-muḍāriʾ al-mabnī and bināʾ al-ḥurūf is presented in classical and contemporary Arabic grammar literature. The objective of this research is to analyze and compare the explanations of this concept in both traditions in order to identify patterns of continuity and development. This study employs a qualitative approach using a library research method by examining major classical works such as Al-Ajurrūmiyyah and Alfiyah Ibn Mālik along with their commentaries, as well as contemporary nahwu references. The findings reveal that classical scholars tend to explain the concept in a concise and rule-oriented manner, focusing on theoretical formulations, while contemporary scholars present it in a more systematic, contextual, and pedagogically oriented way, supported by clearer examples and structured explanations. The study concludes that although the fundamental principles remain consistent across both traditions, there has been significant development in terms of presentation, terminology, and instructional clarity in contemporary Arabic grammar studies. .Keywords: binā’ al-ḥurūf; fiʿil muḍāriʾ; mabnī; classical Arabic grammar; contemporary Arabic grammar